Model Constructs of Optimal Allocation of Financial Resources between the Types of Medical Care in Public Health Sector in a Region - RIZVANOVA, Maria Arturovna; MALIKOV, Rustam Ilkamovich (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
Within socially oriented market economy health care system is of exceptional importance on account of its social focus. The quality of health care delivery and hence population’s health depend on the way it is organized. Utilizing some economic-mathematic modeling techniques, coefficients of priority of different types of health care delivery have been developed (preference coefficients c1, c2,… cn) which enable to facilitate the optimal funding allocation.
Keywords: demography development, model constructs, financial resources, types of medical care, coefficients of preference, optimal allocation of resources in the health care system